The Influence Of Education, Coaching, Work Culture And Employee Attitudes On The Work Performance Of Employees Of Puskesmas Tanjung Raya Muara Enim - Batara, Ivan; Hartati, Ely; Fitriadi, Heri (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
The research was conducted by the author with the aim of knowing and analyzing the influence of education, coaching, work culture and employee attitudes individually and collectively on the work performance of Tanjung Raya Muara Enim Health Center employees. The research method used in this research is a quantitative method using questionnaires distributed to respondents. Test data quality using validity tests, reliability tests, normality tests. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial simultaneous tests and coefficient of determination. The research results showed that education, coaching, work culture and employee attitudes had a significant influence individually and collectively on the work performance of Tanjung Raya Muara Enim Community Health Center employees